Multimodality Characterization of Cancer-Associated Fibroblasts in Tumor Microenvironment and Its Correlation With Ultrasound Shear Wave-Measured Tissue Stiffness in Localized Prostate Cancer - Ageeli, Wael; Zhang, Xinyu; Ogbonnaya, Chidozie N.; Bray, Susan E.; Kernohan, Neil M.; Wilson, Jennifer; Li, Chunhui; Nabi, Ghulam (Frontiers in Oncology, 2022)
Introduction: Growing evidence suggests that the tumour microenvironment (TME) represented by cellular and acellular components plays a key role in the multistep process of metastases and response to therapies. However, imaging and molecular characterisation of the tumour microenvironment (TME) in prostate cancer (PCa) and its role in predicting aggressive tumour behaviour and disease progression is largely unexplored. The study explores the PCa TME through the characterisation of cancer-associated fibroblasts (CAFs) using both immunohistochemistry (IHC) and genomics approaches. This is then correlated with transrectal ultrasound shear wave elastography (USWE) measured tissue stiffness. Patients and methods: Thirty patients with clinically localised PCa undergoing radical prostatectomy for different risk categories of tumour (low, intermediate and high) defined by Gleason score (GS) were prospectively recruited into this study. Prostatic tissue stiffness was measured using USWE prior to surgery. The CAFs within the TME were identified by IHC using a panel of six antibodies (FAP, SMAα, FSP1, CD36, PDGFR α and β) as well by gene expression profiling using tempo-sequence analysis. Whether the pattern and degree of immunohistochemical positivity (measured by Quick score method) and expression of genes characterising CAFs were correlated with USWE and GS measured tissue stiffnesses were tested using Spearman’s rank correlation and Pearson correlation. Results: There was a statistically significant correlation between GS of cancers, the pattern of staining for CAFs by immunohistochemical staining, and tissue stiffness measured in kPa using USWE (p <0.001). Significant differences were also observed in immunohistochemical staining patterns between normal prostate and prostatic cancerous tissue. PDGFRβ and SMAα immunostaining scores increased linearly with increasing the USWE stiffness and the GS of PCa. There was a significant positive correlation between increasing tissue stiffness in tumour stroma and SMAα and PDGFRβ gene expression in the fibromuscular stroma (p < 0.001). Conclusion: USWE measured tissue stiffness correlates with increased SMAα and PDGFRβ expressing CAFs and PCa Gleason scores. This mechanistic correlation could be used for predicting the upgrading of GS from biopsies to radical surgery and response to novel treatments.